THE VOLUME OF THE GENERA AND SPECIES OF THE FAUNA OF SPIDERS (ARANEI) REPUBLIC OF DAGESTAN - G. M. Abdurakhmanov; S. V. Alieva (Юг России: экология, развитие, 2014)
In article the patrimonial analysis of fauna of spiders is given, and also the data on areas of all sorts meeting in territory of Dagestan is cited. By this time for territory of Dagestan it is taped 149 sorts belonging to 32 families from which 22 sorts aren'ted for the first time for research district.